2012
DOI: 10.1080/13607863.2011.615740
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and its comorbidity with depression and somatisation in the elderly – A German community-based study

Abstract: Posttraumatic symptomatology is a common phenomenon in the German elderly population. Especially, subsyndromal disorders are very common and increasing across the age groups. Posttraumatic symptomatology is associated with an increased risk of depressive and somatoform disorders. As posttraumatic symptoms are often neglected in geriatric health care, future effort should address the recognition and treatment of posttraumatic symptoms in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 37 publications
2
41
0
2
Order By: Relevance
“…A community-based study on PTSD and its comorbidity reported that the strongest association of post-traumatic symptomatology was found for somatoform syndromes including SD. Traumatic events without a present post-traumatic symptomatology were significantly related to somatoform symptoms, indicating a possible direct link between trauma and somatization [30]. In accordance with the findings of the latter study, our data showed that a significant proportion of the SD group had current or lifetime PTSD alongside a higher number of traumatic experiences in adulthood (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A community-based study on PTSD and its comorbidity reported that the strongest association of post-traumatic symptomatology was found for somatoform syndromes including SD. Traumatic events without a present post-traumatic symptomatology were significantly related to somatoform symptoms, indicating a possible direct link between trauma and somatization [30]. In accordance with the findings of the latter study, our data showed that a significant proportion of the SD group had current or lifetime PTSD alongside a higher number of traumatic experiences in adulthood (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 94%
“…The close relationships between somatization, exposure to traumatic events and posttraumatic symptoms have been shown in a number of studies [20,21,[28][29][30]. Andreski et al (1998) [20], in their prospective study, indicated that individuals who had traumatic experiences and were eventually diagnosed as having PTSD were more likely to report somatic symptoms compared to those with other psychiatric disorders.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Glaesmer et al (2012) reported a new and recent result on a population-based level of a direct association of trauma with somatization in elderly Germans not mediated by PTSD. Up to now, PTSD and somatization are not assessed in displaced individuals of WW II.…”
mentioning
confidence: 95%
“…1 These conditions, which may persist for more than a decade, often co-occur with mood and anxiety disorders, such as major depression and generalized anxiety disorder. 1,2 In some countries, traumatic experiences related to war in early life are common and may be associated with elevated PTSD symptoms, even decades later. People who have experienced trauma or have PTSD have higher rates of cardiovascular diseases and related risk factors (e.g., hypertension, coron ary artery disease, hyperlipidemia), as well as other common medical conditions (e.g., osteoarthritis, diabetes) 3,4 (Appendix 1, available at www .cmaj .ca /lookup /suppl /doi :10 .1503 /cmaj .120866 /-/DC1).…”
Section: 2mentioning
confidence: 99%